The complete chloroplast genome sequence of Monotropa uniflora (Ericaceae) - XueDie Liu; XingYu Liao; DeQiang Chen; Yu Zheng; Xia Yu; XinYu Xu; ZhongJian Liu; SiRen Lan (Mitochondrial DNA. Part B. Resources, 2020)
Monotropa uniflora is one of the representative plants of Ericaceae family, which was famous for entire translucent and ‘ghostly’ white. Also, unique lifestyle also attracts lots of researchers, which it obtains through fixed carbon from photosynthetic plants via a shared mycorrhizal network. In this study, the complete chloroplast (cp) genome of M. uniflora was assembled and annotated, its full-length is 26,913 bp. Plastid genome contains 31 genes, 14 protein-coding genes, 14 tRNA genes, and 3 rRNA genes. The phylogenetic analyses based on the complete chloroplast genome sequence provided solid evidence that M. uniflora has a close relationship M. odorata. The chloroplast genome presented here will help for further conservation of M. uniflora and other saprophytes.